Effect of Injection Molding Parameters on Mechanical Properties of Keychain Made of Recycled Polypropylene - Mei Hyie, Koay; Kalam, Anizah; Basyar Bin Ramli, Muhammad (International Journal of Engineering and Technology, 2018)
Injection moulding is a common method of plastic processing in which thermoplastic materials can be moulded into arbitrary complex shapes. In order to save the environment, the plastic waste from the injection moulding process needs to be recycled to overcome the non-biodegradable issues. This study is focused on producing the UiTM keychain using injection molding process from the mixing of a specific amount of virgin Polypropylene (vPP) and recycled Polypropylene (rPP). The effect of different injection moulding parameters on mechanical properties of the UiTM keychain on different weight ratio between virgin and recycled Polypropylene was investigated. The effect of injection molding parameters namely holding time and cooling time to the shrinkage of the UiTM keychain was also studied. Mechanical properties were determined by the tensile and flexural tests. Based on the test results, the keychain that contained 80 wt% of virgin Polypropylene and 20 wt% recycled Polypropylene has the most optimum weight ratio. Holding time was the most effective factor to the shrinkage of product. Cooling time was not significant in affecting the shrinkage and tensile properties of PP products. The study helps to promote the usage of recycled PP in the manufacturing industries.Â Â